Resolution of Traumatic Retinal Detachment with Intravitreal Bevacizumab: a case report - Paris, Jai; Macri, Carmelo; Chan, Weng Onn (International Journal of Retina, 2024)
Introduction: Traumatic retinal detachment (RD) without an observable break following ocular trauma is rare. Case Report: A 14-year-old male who suffered from traumatic RD following an explosive injury. Initial examination revealed iridodialysis, vitreous haemorrhage, and impaired visual acuity in the right eye. One week later, the patient developed a macula-off retinal detachment secondary to subretinal exudation without an identifiable retinal break, and a decision was made to trial intravitreal injection (IVI) of bevacizumab before considering surgical intervention. Two days after IVI, significant improvements in subretinal fluid (SRF) were observed, and the retina remained attached during follow-up. The patient's visual acuity and anatomical outcomes improved, and no choroidal neovascularization (CNV) was detected at the 7-month follow-up. Discussion: A rare instance of traumatic RD associated with choroidal rupture, and without an observable retinal break. While the majority of post-traumatic RD is due to pathological breaks, our case highlights the possibility of detachment secondary to exudation resulting from extensive haemorrhage and choroidal ruptura. Conclusion: This case demonstrates the potential efficacy of anti-VEGF therapy in traumatic RD secondary to significant subretinal exudation and offers a less invasive treatment option for select cases, warranting further investigation and long-term studies for a larger patient cohort.